The Glasgow Outcome, APCR and Lipid (GOAL) Pregnancy Study: Significance of Pregnancy Associated Activated Protein C Resistance - Clark, Peter; Sattar, Naveed; Walker, Isobel D.; Greer, Ian A. (Thrombosis and Haemostasis, 2001)
Activated protein C (APC) resistance secondary to Factor V Leiden (FVL) is associated with pregnancy failure and pre-eclampsia (PET). In non-pregnant subjects, the degree of resistance to APC relates to venous thrombosis risk. In pregnancy, resistance to APC occurs in the absence of FVL. We investigated, in an unselected prospective longitudinal study of 1671 pregnant, non-FVL subjects, the relationship of the APC sensitivity ratio (APC:SR) with demographic variables and pregnancy outcome.Lower APC:SR values at 7-16 weeks gestation were observed in subjects who subsequently developed PET (median APC:SR 2.55, IQR 2.29-2.70 vs 2.69, IQR 2.48-2.93, Mann-Whitney U-test p = 0.003) in the current pregnancy. An APC:SR < the median (2.69) at 7-16 weeks was associated with a 2.95-fold increased risk (CI95 1.2-7.4) of PET in the current pregnancy. No relationship between the APC:SR, at any gestation, and fetal loss was observed. An inverse correlation between the APC:SR and birth weight was noted. Higher APC:SRs were observed in blood group O subjects and smokers. An inverse relationship of the APC:SR with age, diastolic blood pressure and total serum cholesterol was observed.
Keywords: APC resistance; pregnancy; pre-eclampsia